Modeling tri-reforming of methane for carbon dioxide utilization and hydrogen production - Ahmed Ashour (3824728) (2025)
The growing demand for low-emission hydrogen production has intensified interest in Tri-Reforming of Methane (TRM) as a promising CO2 utilization pathway. This study presents a multiscale, one-dimensional, steady-state pseudo-homogeneous reactor model developed in Visual Basic for Applications (VBA) to simulate TRM. The uniqueness of this model is that it incorporates nine primary reactions using a Langmuir-Hinshelwood-Hougen-Watson (LHHW) kinetic framework and accounts for transport limitations through overall effectiveness factor calculations, addressing gaps in existing TRM models. Validation against experimental data from the literature yielded a mean absolute percentage error (MAPE) of 1.28 %, confirming the model's accuracy. The model was also applied to simulate Steam Methane Reforming (SMR) and Autothermal Reforming (ATR), demonstrating its adaptability across multiple reforming technologies. Furthermore, catalyst scalability was assessed across particle sizes up to 10 mm. This work provides a flexible and robust simulation tool for evaluating catalyst performance, optimizing reactor design, and supporting the development of TRM-based hydrogen production systems and related reforming processes. Other Information Published in: Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.energy.2025.137977